Resenha - Raposa, Michael L. (Cognitio: Revista de Filosofia, 2021)
PIHLSTROM, Sami. Pragmatic realism, religious truth, and antitheodicy: on viewing the world by acknowledging the other. Helsinki: Helsinki University, 2020. 195 p.